2004
DOI: 10.1103/physreva.70.032113
|View full text |Cite
|
Sign up to set email alerts
|

Lindblad- and non-Lindblad-type dynamics of a quantum Brownian particle

Abstract: The dynamics of a typical open quantum system, namely a quantum Brownian particle in a harmonic\ud potential, is studied focusing on its non-Markovian regime. Both an analytic approach and a stochastic wavefunction approach are used to describe the exact time evolution of the system. The border between two very different dynamical regimes, the Lindblad and non-Lindblad regimes, is identified and the relevant physical variables governing the passage from one regime to the other are singled out. The non-Markovia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(152 citation statements)
references
References 48 publications
5
147
0
Order By: Relevance
“…From previous results [4,32,33] we expect to see different types of dynamics in the r ≪ 1 and r ≫ 1 regimes. Since we are interested in the non-Markovian dynamics occurring at time scales ω c t ≤ 1, we can use the secular master equation (7) when r ≪ 1, since in this case the secular approximation holds in the non-Markovian time scales.…”
Section: B Modeling the Reservoirmentioning
confidence: 99%
“…From previous results [4,32,33] we expect to see different types of dynamics in the r ≪ 1 and r ≫ 1 regimes. Since we are interested in the non-Markovian dynamics occurring at time scales ω c t ≤ 1, we can use the secular master equation (7) when r ≪ 1, since in this case the secular approximation holds in the non-Markovian time scales.…”
Section: B Modeling the Reservoirmentioning
confidence: 99%
“…The analytical expression for the heating function is given by [18,46] n(t) = e −Γ(t) n(0) + 1 2 e −Γ(t) − 1 + ∆ Γ (t), (20) where Γ(t) and ∆ Γ (t) are defined as…”
Section: Heating Of a Quantum Brownian Particle A Markovian Thermmentioning
confidence: 99%
“…The QBM model is one of the few models of open quantum systems amenable to an analytical solution [1,2,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[32] it has been shown that, going to low temperature, the position of the Brownian particle governed by the BMME experiences genuine squeezing along x in the Wigner function representation, i.e., δ x < 1. Similar squeezing effects are pointed out in [18], by studying the numerical solution of the exact ME. In the case of the LME, it was checked numerically that δ x introduced in Eq.…”
Section: T) (21)mentioning
confidence: 67%
“…Here, one of the unsolved issues regards the problem of the quantum-to-classical transition, i.e., the question of how do classical features we experience in the macroscopic world arise from the underlying quantum phenomena [3,[11][12][13]. Most of the theories addressing the emergence of the classical world deem it a consequence of the coupling of quantum systems with the environment [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%